Tame Problems, Wicked Possibilities: Interpreting the Distinction between Wicked and Tame Problems through the Cybernetic Concepts of Variety and Constraint - Ben Sweeting (She Ji: The Journal of Design, Economics and Innovation, 2024)
The distinction between wicked and tame problems has been a major influence on design and numerous other fields since it was developed in the late 1960s and early 1970s by design theorist Horst Rittel and urban designer Melvin Webber. The characteristics of wicked problems continue to resonate today, helping make sense of the complexities of contemporary challenges. Wicked and tame refer to types (rather than degrees) of difficulty, but what defines these types is not simply the domains in which problems occur, as in the dichotomy between scientific and social contexts originally put forward by Rittel and Webber. To clarify the distinction between wicked and tame, I ground it in the cybernetic concepts of variety and constraint, building on Rittel’s references to the cybernetician Ross Ashby. Understood in this way, wicked and tame do not refer to problems, or to the situations in which problems arise. Rather, wickedness and tameness are dynamics of possibilities (variety) in how multiple aspects of problems are perceived and responded to across the relationships in which designing (in its broadest senses) is embedded.